Energy efficiency and COVID-19: a systematic literature review and bibliometric analysis on economic effects - Yao, Xuan; Xu, Zeshui; Wang, Xinxin; Wang, Lina; Škare, Marinko (Technological and Economic Development of Economy, 2024)
The Corona Virus Disease 2019 (COVID-19) epidemic has deferred global progress in energy efficiency to a decade-long low, posing a threat to the achievement of international climate goals, and also profoundly affected the development of economics. To gain insight into the research frontiers and hotspots in energy efficiency and COVID-19, a systematic literature review and bibliometric analysis on economic effects are performed with the help of the bibliometric tools VOSviewer and Bibliometrix. This paper selects all the publications retrieved based on the subject terms in the Web of Science core collection. Firstly, this article performs a performance analysis of related publications to present the development and distribution of energy efficiency and COVID-19 from research areas, relevant sources, and influential articles. Afterward, a visual analysis of the literature called science mapping analysis is implemented to display the structural and dynamic organization of knowledge in energy efficiency and COVID-19 research. In the end, detailed discussions of two research hotspots and some theoretical and practical implications are concluded in the systematic literature review and bibliometric analysis findings, which may contribute to further development for researchers in the field of energy efficiency and eventually propel the progress of society and economy in an all-round way.First published online 06 October 2023